ANALYSIS OF HOW TEACHERS MOTIVATE STUDENTS IN THEMATIC LEARNING IN PUBLIC ELEMENTARY SCHOOL 37 PEKANBARU - Rizka Azimah; Mahmud Alpusari; Neni Hermita (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
This study aims to find out what is the most dominant way teachers use in motivating students on thematic learning. This research was conducted at Public Elementary School 37 Pekanbaru. This type of research is descriptive quantitative research. The subjects in this study were class teachers at Public Elementary School 37 Pekanbaru. The data was collected using observation techniques, and research questionnaires. Based on the results of data analysis, it can be known that the way teachers motivate students in thematic learning at State Elementary School 37 Pekanbaru consists of nine indicators, namely giving a figure with a percentage of 11.9%. Gift Giving Indicator with a percentage of 10.0%. Competition Indicator with a percentage of 11.4%. Indicator Of Growing Ego-involvement with a percentage of 10.5%. The Indicator Gives a Replay with a percentage of 12.0%. Indicators Knowing Learning Outcomes with a percentage of 11.5%. The Indicator Gives Praise with a percentage of 12.0%. Indicators Provide Penalties with a percentage of 9.7%. And the Indicator Gives Desire to learn with a percentage of 11.0%. So the average percentage of the overall percentage is 87.5% and belongs to the category always. This means that most teachers always use nine ways to motivate the students during the teaching process in the school. So it can be concluded that the way teachers motivate students in the most dominant thematic learning used by teachers is by giving praise and giving repeats because with the same percentage